Numerical investigation of a two-bladed vertical-axis turbine operating in a confined channel - Leandro Duarte; Nicolas Maguin; Guilhem Dellinger; Nicolas Dellinger; José Vazquez (Energy Conversion and Management: X, 2022)
The energy harvesting performance of a hydrokinetic turbine in a confined channel has been investigated through numerical simulations. It consists of a two-bladed vertical-axis turbine with a NACA0015 profile. Fluid dynamics are reproduced by a 2D numerical model solving the unsteady RANS equations through a finite volume approach in OpenFOAM-v6. Following a numerical sensitivity analysis, the baseline model has been validated with respect to reference data for an unconfined turbine with similar design. The model has then been employed for assessing the influence of the main design parameters – namely blade-channel gap ε0, solidity σ and tip-speed ratio λ – on the performance of the turbine. First, a parametric study on the plane λ×σ revealed that best performance is obtained at high solidity and low tip-speed ratios. In a range of solidities from 0.06 up to 0.48, the optimal value of tip-speed ratio – which is considerably higher when compared with unconfined turbines – is precisely identified. Finally, the effects of the blade-channel gap ε0 on the performance of the turbine has been investigated as well. It has been found that ε0 should be set as small as possible in order to maximise energy harvesting. Moreover, numerical results allowed for estimating a limit value of ε0>9 over which the performance of a turbine operating in a confined channel should match that of an unconfined turbine.